Pengembangan Aplikasi Front End Pengguna Whatsapp Gateway Jurusan Informatika Universitas Tanjungpura - Ayub Rahmanda; Yus Sholva; Morteza Muthahhari (Sinergi : Jurnal Ilmiah Multidisiplin, 2025)
This research aims to develop an intuitive and user-friendly front end application to utilize the WhatsApp Gateway service at the Informatics Department, Tanjungpura University. The development methodology used is the Rational Unified Process (RUP) through two iterations. The first iteration focuses on implementing core features such as WhatsApp multi-account management, phone book, messaging (direct and group), keyword-based auto-reply, and user profiles. The second iteration continues with responsive design, multi-role login, a landing page, enhanced auto-reply using Gemini API, and scheduled messaging. Black box testing with the Equivalence Class Partitioning (ECP) technique was applied in each iteration to ensure application functionality. The test results show that the application functions well according to the specified requirements. This application development is expected to facilitate end-users, especially within the informatics department, in utilizing the WhatsApp Gateway service without needing in-depth technical expertise. This application also contributes to increasing the efficiency of information dissemination through WhatsApp. Keywords: Front end, WhatsApp Gateway, Rational Unified Process (RUP), Gemini API, Black Box Testing, Auto-reply, Scheduled Messages   Abstrak Penelitian ini bertujuan untuk mengembangkan aplikasi front end yang intuitif dan mudah digunakan untuk memanfaatkan layanan WhatsApp Gateway di Jurusan Informatika Universitas Tanjungpura. Metodologi pengembangan yang digunakan adalah Rational Unified Process (RUP) melalui dua iterasi. Iterasi pertama difokuskan pada implementasi fitur inti seperti pengelolaan multi-akun WhatsApp, buku telepon, pesan (langsung dan grup), autoreply berbasis kata kunci, dan profil pengguna. Iterasi kedua melanjutkan pengembangan dengan penambahan desain responsif, login multi-peran, landing page, peningkatan fitur autoreply menggunakan Gemini API, dan pesan terjadwal. Pengujian black box dengan teknik Equivalence Class Partitioning (ECP) digunakan pada setiap iterasi untuk memastikan fungsionalitas aplikasi. Hasil pengujian menunjukkan bahwa aplikasi telah berfungsi dengan baik sesuai dengan spesifikasi yang ditetapkan. Pengembangan aplikasi ini diharapkan dapat mempermudah pengguna akhir, khususnya di lingkungan jurusan informatika, dalam memanfaatkan layanan WhatsApp Gateway tanpa memerlukan keahlian teknis yang mendalam. Aplikasi ini juga memberikan kontribusi dalam meningkatkan efisiensi penyebaran informasi melalui media WhatsApp. Kata kunci: Front end, WhatsApp Gateway, Rational Unified Process (RUP), Gemini API, Pengujian Black Box, Autoreply, Pesan Terjadwal